A fruity bowel obstruction: ingested dehydrated apple as a cause for small bowel obstruction - Page, Daniel; Dauway, Emilia (International Surgery Journal, 2020)
Small bowel obstructions are common acute surgical presentations often as a result of intraabdominal adhesions or herniations; rarer causes include malignancies, strictures, foreign bodies and bezoars. Phytobezoars (bezoars composed of undigested plant material) account for<4% of small bowel obstructions. Here we report an unusual case of a 56-year-old male with a virgin abdomen presenting with a small bowel obstruction, a CT scan of his abdomen and pelvis was suggestive of a closed loop small bowel obstruction. The patient progressed to have an emergency laparotomy and was found to have multiple intraluminal obstructing foreign bodies within the distal ileum. On making an enterotomy to remove and examine these, they were found to be rehydrated apple segments that the patient had ingested in the dehydrated form several hours earlier. This is an example of a phytobezoar causing bowel obstruction, contributing factors to the occurrence of these include poor gastrointestinal motility and problems of mastication; in this instance the patient had poor dentition that likely pre-disposed him to this problem.